Groupware for Collaborative Tailoring - Fernández, Alejandro (2005)
In everyday work, teamwork in the presence of the tools, the resources, and the processes that enable work is mostly transparent to the workers. They center their attention on performing work. However, a noticeable change in the work conditions, in the required quality of the product, or in the perceived results of work, may be experienced as a breakdown that brings teamwork to the center of attention. To deal with breakdowns it is currently common practice to include tailoring facilities in groupware systems. The extent to which these facilities are provided, and the way in which they are implemented, determine the power users have to change the groupware system. Determining these facilities has been the focus of most research on tailorability in CSCW. How collaborative tailoring (defined as, collaboration for and in tailoring) can be facilitated remains as yet undetermined. This thesis tackles the problem of the lack of computer support for dis- tributed team members that need to perform tailoring in the context of team- work. The challenge of tailoring in the context of teamwork is to understand and support the needs of the group members, from the moment they encounter a breakdown during work until they have enacted the changes they deem nec- essary. This thesis is based on the premise of participation as a means to achieve acceptance of change. The approach to support collaborative tailoring of team- work presented in this thesis consists of a method for collaborative breakdown handling, a selection of specific groupware tools to be used for the deliberation activities defined by the method, and guidance in the form of scaffoldings for the application of the method. Breakdowns can also occur during tailoring. To deal with breakdowns that occur during tailoring, the method, the tools, and the scaffolding can be tailored. The proposed support for collaborative tailor- ing of teamwork is delivered as a stand-alone groupware system for collaborative tailoring. The system can be deployed along existing groupware systems, thus extending them with support for collaborative tailoring. This thesis exceeds related work by approaching tailoring of teamwork as a social system with a model that explains tailoring as the result of collaborative breakdown handling. The requirements of communication, collaboration, co- operation and coordination, and negotiation observed in the social system are supported by the corresponding technical system. The approach in this thesis is not limited to its application in a particular scenario or groupware system. The only requirement is that the target system/scenario can be tailored. The approach has been conceived to enable and support its own evolution as the result of its tailoring.